Telecontrolling Smart Fish Feeder Berbasis Mikrokontroler Dan Aplikasi Android - Prayogo Khanua Almufaridz; Mila Kusumawardani; Rachmad Saptono (Politeknik Negeri Malang, 2021)
Indonesia is a country known for its aquaculture. Regular feeding is influential in a good farming management system to obtain quality fish. However, the feeding system is still oriented to human resources that are still manual, resulting in an erratic feeding schedule and size, making it different for each feeding. Feeding planning must be precise so that fish growth is fast. In this research, an automatic fish feeder called